2013
DOI: 10.1136/bjophthalmol-2013-304450
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Ultra wide-field intravenous fundus fluorescein angiography in infants using the Optos P200MA scanning laser ophthalmoscope

Abstract: We have shown that UWF-IV-FFA can be successfully and safely performed in infants using the Optos P200MA system. It is a feasible new alternative to RetCam for obtaining an IV-FFA in the outpatients setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…11 This series is the first to describe non-contact ultrawidefield retinal imaging of infants with suspected AHT. The Optos P200MA scanning laser ophthalmoscope effectively documented acute and chronic AHT-related retinal haemorrhages, accurately defined the anatomical location of haemorrhage in one infant who was referred for consideration of vitrectomy, and excluded retinal haemorrhages and consequently AHT in a fifth infant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 This series is the first to describe non-contact ultrawidefield retinal imaging of infants with suspected AHT. The Optos P200MA scanning laser ophthalmoscope effectively documented acute and chronic AHT-related retinal haemorrhages, accurately defined the anatomical location of haemorrhage in one infant who was referred for consideration of vitrectomy, and excluded retinal haemorrhages and consequently AHT in a fifth infant.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Mydriasis was achieved with topical phenylephrine 2.5% and cyclopentolate 0.5%. Topical proxymetacaine 0.5% was instilled into each eye followed by insertion of a paediatric Lieberman speculum to part the eyelids, secured to the temple with Micropore tape.…”
Section: Retinal Imaging Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 16 It has been shown that ultrawide-field FA (UWFA) is useful for the assessment of several retinal pathologies 17 including retinal vein occlusions, 18 diabetes, 19 , 20 uveitis, 21 retinal vasculitis, 22 choroidal masses, 23 , 24 retinal detachment, 25 and retinopathy of prematurity. 26 …”
Section: Introductionmentioning
confidence: 99%